Labor mobility and remittances in Asia and the Pacific during and after the COVID-19 pandemic - Kikkawa, Aiko; Kikkawa, Aiko; Sugiyarto, Guntur; Villafuerte, James; Kim, Kijin; Narayanan, Badri; Gaspar, Raymond (Manila,Philippines Asian Development Bank, 2021)
Remittance inflows to Asia and the Pacific declined by 2% in 2020. They are expected to recover at a growth rate of 6.7% for 2021 and 5.9% in 2022. The brief provides policy recommendations to help improve labor migration governance and maximize the economic potential of migration and remittances while addressing ongoing challenges.
Keywords: Emigrant remittances -- Asia and the Pacific; Investments, Foreign -- Asia and the Pacific; COVID-19 Pandemic, 2020 -- Economic aspects